Implementation of the Adiwiyata Program and GPBLHS: Fostering Environmental Awareness and Sustainability in Schools - Sari, Indri Gus Permata; Frinaldi, Aldri; Rembrandt, Rembrandt (Science and Environmental Journal for Postgraduate, 2024)
The Adiwiyata program, initiated by the Ministry of Environment and Forestry in 2006, aims to promote environment-focused education in primary and secondary schools. In 2019, this initiative evolved into the Environmental Care and Culture Movement in Schools (GPBLHS), emphasizing collaborative, systematic efforts to foster environmental awareness, sustainable practices, and disaster resilience in school communities. This study adopts a qualitative approach to examine the implementation of GPBLHS in a school awarded National Adiwiyata status in 2017. Data were collected through interviews, document analysis, field observations, and focus group discussions involving principals, teachers, students, and other stakeholders. Data analysis included reduction, presentation, and conclusion drawing, supported by triangulation to ensure accuracy. Findings reveal that the program’s success relies on environmentally based policies, integrated curricula, participatory activities, and eco-friendly facilities. Key challenges include limited resources, low environmental awareness, and curriculum gaps. Effective leadership and collaboration among stakeholders are critical for program sustainability. The study highlights the importance of regular evaluation, socialization, and partnerships with external organizations to enhance impact. Overall, GPBLHS serves as a medium to cultivate environmentally conscious behaviors and create healthy, sustainable learning environments, while shaping responsible future generations.